Assessment approach of Development Education and Global Citizenship Education - M. Inmaculada PASTOR-GARCÍA; Alberto A. LÓPEZ-TORO; Félix MORAL-TORANZO (Revista Iberoamericana de Estudios de Desarrollo, 2019)
International Cooperation requires an assessment of Development Education as a guide to understanding, evaluating and making decisions that improve the efficacy and impact of its actions. This study focuses on demonstrating how a tool that is used in formal education can also be used to assess Development Education and Global Citizenship Education (DEGCE). Through a descriptive analysis, we compared DEGCE with the social and citizenship competences assessed in the Spanish region of Andalusia. We found a strong relationship between them in terms of content, teaching-learning method, and evaluative approaches. This implies that the diagnosis of social and citizenship competences not only serves as a model, or example, for DEGCE assessment, but it also provides relevant and useful information to evaluate its present state.